Cell Phones for College Teaching: A Literature Review - Tenzin Yeshi; Steven D. Aagard (Adult Education Research Conference, 2011)
Cell phone is the fastest growing technology among young adults. However, cell phones are considered more as a distraction in the classroom than a tool to support college student’s learning. Cell phones can be noisy and distracting, but they can also be an aid to learning (Docksai, 2009). Although cell phone is the most preferred mobile device of college students and its ownership are widespread, cell phones in general are still underappreciated in the college settings. From the literature review, majority supported the use of cell phone to enhance college students’ learning and interaction despite some prevailing limitations.
Keywords: Cell phones; adult education; college students; mobile device